Analysis of the Application of Profit Sharing Method from A Javanese Cultural Perspective in South Sumatera - Muhammad Aras Prabowo; Baeby Aulia Frisca Yanti; Habsyah Fitri Aryani (Trescode Green Organization, 2025)
This study aims to analyze the application of the accountant’s codeof ethics in the Javanese cultural profit-sharing method in SouthSumatera. This study uses a literature study, or literature review,and analyzes data with a descriptive qualitative approach. Theliterature sources used include journal articles that are relevant tothe research topic. This study reveals that there are three thingsrelated to profit-sharing including (1) maro or paron, (2) farmlaborers, (3) wong tani. These three values strengthen theapplication of the accountant’s code of ethics in the profit-sharingmethod.